Do FinTech, Financial Inclusion, and Institutional Quality Reduce Income Inequality? Panel Data Evidence from Asian Countries - Bishwakarma, Sagar; Nepal, Pramshu; Bista, Smeeth (Economic Journal of Nepal, 2024)
Asia is one of the fastest-growing economies in the world, but it consistently lags behind the global average in terms of FinTech penetration and financial inclusion. Improved financial inclusion and enhanced FinTech are expected to reduce income inequality. In this study, we utilize data from four rounds of the Global Findex survey conducted in 2011, 2014, 2017, and 2021, covering 39 countries in Asia with 143 observations. We applied various models, including unbalanced pooled, fixed/random, with different sets of variables such as institutional quality, schooling, GDP, population, government expenditure, trade, and inflation, to assess the relationships across FinTech, financial inclusion, and income inequality. Our findings suggest a reciprocal relationship between FinTech and financial inclusion. FinTech enhances financial inclusion, which, in turn, positively affects the development of FinTech. Moreover, our analysis reveals that financial inclusion significantly reduces income inequality, but we could not confirm the direct effect of FinTech on income inequality reduction in the Asian regions. Institutional quality emerged as a powerful measure in reducing income inequality. Similarly, mediating variables such as GDP and trade also reduce income inequality significantly. Therefore, the government may emphasize investing in Fintech infrastructure, launching financial inclusion programs through public-private partnerships, promoting institutional quality, and expanding trade activities to support employment opportunities, particularly in developing economies in Asia. These joint efforts to reduce income inequality help in poverty reduction.